Modelagem dinâmica temporal para a avaliação da disponibilidade hídrica e seus efeitos na sustentabilidade do sistema da sub-bacia do córrego do Boi Branco - SP - Ferreira, Alexandra Vaz [UNESP] (2014)
This study aimed to formulate a model in order to analyze the water resources sustainability at Boi Branco sub-basin using System Dynamics (SD) methodology. The SD allows to represent the behavior of complex systems including relation between cause and effect, and through feedback linkages mathematical computational simulation models allowing to control and tap a real system. The Boi Branco sub-basin has a drainage area of 80.71 km2; its right arm is located in the southeast city of Paranapanema and its left arm in the southeast city of Itai; between longitudes 48º48'39'' and 48º 55'39'' and latitudes 23º36'01'' and 23º29'00'', respectively. 20.09 km2 of the sub-basin is irrigated by center pivot and, cultivated with wheat, cotton, corn, beans, potatoes and soybeans. Simulations to determine the supply, demand and water sustainability index can be grouped in three scenarios: effects of precipitation with a probability of 75% and 50% and the efficiency of the irrigation system, and considering an ecological flow of 1/40 and 1/10 for the first two scenarios and for the latter scenario, the behavior of rainfall equal to the first 10 years of the series from 1971 to 1980. The results show that water demand is greater than the potential supply of surface water; it reflects vulnerable conditions which classify it as critical, in accordance to Article 14 of Law 9034. It is concluded: 1) Considering only the surface water supply in the sub-basin and irrigated agriculture, water resources are not sustainable in all scenarios; 2) The sustainability of water resources in Boi Branco sub-basin, excluding weather factors will only be possible if farmers include groundwater resources to supplement surface uptake; 3) The efficiency of 4 irrigation systems equal to or greater than 80% reduces water demand; 4) The instream flow 1/40 could be used as a basis for process management, in view of the multiple use ...